Hubungan Karakteristik dan Kepribadian Anak dengan Kejadian Bullying pada Siswa Kelas V di SD “X” di Kabupaten Badung - Diyantini, Ni Kadek; Yanti, Ni Luh Putu Eva; Lismawati, Sagung Mirah (Coping: Community of Publishing in Nursing; Vol 3 No 3 (2015): JURNAL EDISI SEPTEMBER-DESEMBER 2015, 2015)
The phenomenon of bullying in children most often occurred in schools, especially primary schools. The final stages of school age (10-12 years) are very vulnerable involved in bullying. Many factors affect bullying in children, both internal and external of children. This study aims to determine the relationship between child’s characteristics and personalities with bullying in fifth grade students in the elementary school "X" in Badung Regency. This is correlational descriptive study with cross sectional design. The samples in this study are 55 people that selected by simple random sampling. The results showed that the majority of children (58,2%) are involved in bullying at school. But the results of Spearman Rank and Lambda correlation test showed no significant correlation between the child’s characteristics and personalities with bullying in students. Therefore, it is very important for the school and parents to control the children activities.